2018
DOI: 10.1088/1361-6463/aae752
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing dyes for super-resolution fluorescence microscopy

Abstract: In recent years, optical microscopy techniques have emerged that allow optical imaging at unprecedented resolution beyond the diffraction limit. These techniques exploit photostabilizing buffers to enable photoswitching and/or the enhancement of fluorophore brightness and stability. A major drawback with the use of photostabilizing buffers, however, is that they cannot be used in live cell imaging. In this paper, we tested the performance of self-healing organic fluorophores, which undergo intramolecular photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 58 publications
0
39
0
Order By: Relevance
“…[11] Previous work on STORM systems has produced simpler and less toxic protocols, typically involving self-healing dyes as well as heavy-atom-containing quantum dots. [12][13][14] Additionally, it has been shown that certain probes can be used for live-cell STORM, but only in specific organelles, such as the mitochondria, that have increased levels of thiol compound glutathione. [15] The Tinnefeld group described an experimental strategy to induce blinking with only one excitation light source by using an imaging buffer that contains both oxidizing and reducing agents.…”
Section: Doi: 101002/adma202006829mentioning
confidence: 99%
“…[11] Previous work on STORM systems has produced simpler and less toxic protocols, typically involving self-healing dyes as well as heavy-atom-containing quantum dots. [12][13][14] Additionally, it has been shown that certain probes can be used for live-cell STORM, but only in specific organelles, such as the mitochondria, that have increased levels of thiol compound glutathione. [15] The Tinnefeld group described an experimental strategy to induce blinking with only one excitation light source by using an imaging buffer that contains both oxidizing and reducing agents.…”
Section: Doi: 101002/adma202006829mentioning
confidence: 99%
“…By harnessing the resolving power of super-resolution optical microscopy, our understanding of synapse structure and function has taken big leaps in recent years. With the incessant quest for further refinements in terms of better hardware, increasingly powerful processing algorithms (e.g., Xu et al, 2017), or deep learning strategies (Ouyang et al, 2018;Wang et al, 2019;Jin et al, 2020), fluorophores with improved or tailored photophysical properties (e.g., Minoshima and Kikuchi, 2017;Thiel and Rivera-Fuentes, 2018;Halabi et al, 2019;Kozma and Kele, 2019;Velde et al, 2019;Xu et al, 2020), and, quite likely, yet new and revolutionary technical approaches altogether, the limits of what can be resolved today are bound to keep shrinking. In parallel, the evolution of strategies for high-throughput SRM are allowing faster imaging of increasing numbers of simultaneous targets over larger sample areas (Guo et al, 2019;Mahecic et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…What we seem to be observing is the effect of slight variations in buffer conditions on the dye photophysics, which may be due to diffusion-limited reactions between the thiol and the dyes or slight variations in oxygen concentration. Improved buffer conditions [32] or self-healing dyes [33,34] could mitigate this variability, but the message is clearly that one must be cautious both in performing and applying this calibration to a molecular counting experiment.…”
Section: Calibration Of λmentioning
confidence: 99%